Telomeric features of Theileria parva mitochondrial DNA derived from cycle sequence data of total genomic DNA - Shukla, G.C.; Nene, Vishvanath M. (Elsevier, 1998)
We have previously reported on characterisation of mitochondrial DNA (mtDNA) of Theileria parva (1), an intracellular protozoan parasite of cattle (reviewed in (2). The mtDNA encodes ORFs for apocytochrome b and polypeptides I and III and cytochrome oxidase, contains fragmented rRNA genes and exists as a 7.1 kbp linear DNA molecule. The mtDNA was only amenable to cloning following brief treatment with Bal31 exonuclease and partial sequence data indicated the presence of terminal inverted repeat (TIR), sequences which could have made the intact molecule refractory to cloning (1). The limited protein coding capacity, rRNA gene fragmentation and TIR sequences of the parasite mtDNA is similar to that described for the 15.8 kbp linear mtDNA of Chlamydomanas reinhardtii, a unicellular green algae (3). In an attempt to complete the sequence analysis of the ends of the parasite mtDNA we have taken advantage of cycle sequencing. Rather than using purified mtDNA as template, we reasoned that since the T. parva genome is only about 10 (7) bp (4,5), and parasite mtDNA is present in multiple copies (1), we should be able to employ cycle sequence analysis of total genomic DNA to obtain mtDNA sequences. This method has been described for obtaining nucleotide sequence from a cloning vector in a single bacterial colony or bacteriophage plaque (6). Total genomic DNA was isolated from bovine red blood cells infected with the piroplasm stage of T. parva (7) and an aliquot of the DNA was digested to completion with HindIII. This restriction enzyme cleaves the mtDNA once (1) and was used to reduce the viscosity of the DNA solution. The digested DNA was exracted with phenol and chloroform, precipitated with absloute cold ethanol, rinsed with 70 percent ethanol (8) and then suspended in water at a concentration of 1 mg/ml. A 5 mu-gamma sample of the genomic DNA was subjected to cycle sequencing using the fmol DNA sequencing ssystem (Promega), following the manufacturer's instructions. Briefly, 10 pmol of 33P labelled primer was used with Taq DNa polymerase, template and dNTP/ddNTP mixes in the standard buffer. The microtitre plate was placed in a programmable thermal cycler preheated to 95 degree centi-grade and the cycle sequencing program started. Cycling profile conditions consisted of denaturation for 1 min at 95 degree centi-grade followed by 30 cycles of 30 s at 94 degree centi-grade, 30 s at 55 degree centi-grade and 1 min at 72 degree centi-grade. After adding stop buffer the sequencing reactions were denatured at 78 degree centi-grade for 2 min and electrophoresed on a 6 degree centi-grade polyacrylamide, 7 M urea gel at 50 W (8).